An approach for Reverse Engineering from Web Applications into the Language of the Domain using the LEL Glossary - Granizo Rodríguez, Angela Verónica (2024)
Requirement engineering plays a crucial role in the software lifecycle, since errors made in the requirements require significant effort to be corrected in later stages. The main source of requirements is people; however, it is common to analyze existing applications when developing new software. This is particularly the case in the process of reengineering. On the other hand, the language of the domain is essential to understanding the domain and thus comprehending the requirements. Language Extended Lexicon (LEL) is a structured glossary designed to capture this language. This paper proposes an approach for obtaining the language of an application domain from a web application using the LEL glossary. The process comprises three main activities: general analysis of the web application, domain language capture, and the verification of the generated domain language. Additionally, this paper describes a web browser extension tool designed to support the process. Finally, the paper presents the results of a preliminary evaluation with promising outcomes regarding the applicability of the approach.